Newborn screening: a review of history, recent advancements, and future perspectives in the era of next generation sequencing. Issue 6 (December 2016) - Almannai, Mohammed; Marom, Ronit; Sutton, V. Reid
Abstract : Purpose of review: The purpose of this review is to summarize the development and recent advancements of newborn screening. Recent findings: Early initiation of medical care has modified the outcome for many disorders that were previously associated with high morbidity (such as cystic fibrosis, primary immune deficiencies, and inborn errors of metabolism) or with significant neurodevelopmental disabilities (such as phenylketonuria and congenital hypothyroidism). The new era of mass spectrometry and next generation sequencing enables the expansion of the newborn screen panel, and will help to address technical issues such as turnaround time, and decreasing false-positive and false-negative rates for the testing. Summary: The newborn screening program is a successful public health initiative that facilitates early diagnosis of treatable disorders to reduce long-term morbidity and mortality.